Questionnaire design : how to plan, structure and write survey material for effective market research - Brace, Ian (London ; Philadelphia : Kogan Page, 2008)
Questionnaires are a vital tool of market research. They can draw accurate information from respondents, facilitate data processing and provide a standard against which comments and attitudes can be measured. This book explains how to plan, structure and write a questionnaire to achieve these aims.
Includes bibliographical references (p. [286]-293) and index.
Keywords: Market surveys -- Methodology; Questionnaires -- Methodology